Association of occlusal support with type 2 diabetes: A community-based study - Da, Dongxin; Ge, Suyu; Zhang, Hao; Zeng, Xiaoli; Jiang, Yiwei; Yu, Jin; Wang, Huning; Wu, Wanqing; Xiao, Zhenxu; Liang, Xiaoniu; Ding, Ding; Zhang, Ying (Frontiers in Endocrinology, 2022)
Occlusal support was proved to be associated with type 2 diabetes. Our aim was to investigate the association between the Eichner index and the prevalence of type 2 diabetes. We included 715 participants with oral health examination in the Shanghai Aging Study. The occlusal support status was determined by the number of func-tional occlusal support areas and Eichner index classifications. Those with fasting plasma glucose ≥126 mg/dL and/or haemoglobin A1c ≥6.5% and/or current medica-tions for type 2 diabetes with relevant medical history were diagnosed with type 2 diabetes. Multiple logistic regression models were used to analyze the relationship between occlusal support status and type 2 diabetes. The average age of 715 partici-pants was 73.74±6.49 years old. There were 84 diabetics with 1.71 occlusal support-ing areas on average. Seven hundred and fifteen participants were divided into 3 groups according to Eichner classifications: Eichner group A with 4 occlusal func-tional areas, Eichner group B with 1-3 occlusal functional areas or 0 area with ante-rior occlusal contact, and Eichner group C with no functional occlusal contact. Blood glucose level was significantly lower in participants of Eichner group A compared to those in group B or C. The ordinal logistic regression showed more occlusal sup-porting areas were significantly associated with less type 2 diabetes cases with an Odds Ratio(OR) of 0.253(95%CI 0.108-0.594) after adjusting covariates. Partici-pants in Eichner group A had a significantly much lower OR of 0.078 for type 2 dia-betes (95%CI 0.009-0.694) compared to those in Eichner group C after adjustment. The number of functional occlusal support areas might be inversely related to the blood glucose level and the prevalence of type 2 diabetes.